Port Pricing. Considerations on Economic Principles and Marginal Costs - H. Meersman; E. Van de Voorde; T. Vanelslander (European Journal of Transport and Infrastructure Research, 2003)
Pricing by ports and operators within ports is considered quite a complex and untransparant matter, and as such it is sometimes perceived as archaic. This often results in debates about subsidies, captive markets and the dredging and deepening of maritime access routes, raising questions concerning potential distortion of competition and/or abuse of monopolistic power. This paper starts from the most important scientific literature on port pricing (and port competition), and adds new empirical results while calculating the marginal cost of a port call. A distinction is made between four elements of marginal costs in port operations, being costs for provision of infrastructure, costs associated with the use of the transport mode, costs for supplying port services, and external costs. This material may constitute the basis for a meaningful debate on the implementation of a pricing approach that is grounded on the marginal cost principle.